Motor tele-rehabilitation in post-stroke patients. - Piron, Lamberto (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
The advanced communication technology may allow rehabilitative interventions to patients living at home from a remote provider. We evaluated the effects of a tele-rehabilitation system for the therapy of arm motor impairments due to a stroke. Experimental observational study. We selected five patients suffering from mild/intermediate arm motor impairments due to a long-lasting ischaemic stroke. Two workstations were utilized, one in the patient's house and the other in the rehabilitation hospital, connected through the phone lines. A virtual reality based software allowed the patient to perform adequate motor tasks created by the physiotherapist. During performance, the patient could see not only their movement but also the correct trajectory that they had to accomplish. The feedback derived from the patient's action, its outcome, and feedback from the supervision of the physiotherapist may favour the acquisition of new motor abilities.The arm motor performance and the activities of daily living were evaluated using the Fugl-Meyer and Functional Independence Measure scale, together with the determination of the velocity and duration of 10 representative reaching movements. Subjects underwent the tele-rehabilitation programme for 4 weeks. The therapy significantly improved the Fugl-Meyer mean score, the mean duration and the velocity of the movements, but not the Functional Independence Measure scale score. These results indicated that this tele-rehabilitation system did not appear to adversely affect rehabilitation; rather it may improve arm motor deficits due to a stroke. If these evidences are further confirmed, tele-rehabilitation may represent a new home-based therapy to treat disabled people.